Pelatihan Seni Jatung Utang di Era Modern: Menghidupkan Kembali Musik Tradisional Kalimantan di Tengah Arus Modernisasi Digital - Muhlis, Muhlis; Diana Septika, Hety; Gunawan, Asril; Ibnu Sa’ad, Muhammad; Al Hafidh, M. Hadi; Irsyadus Sholihin, Afif; Humaira Dzakirah, Farsya; Irwanto; Surianto, Eri (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community service program was implemented through the Program Inovasi Seni Nusantara (PISN) an Archipelago Art Innovation Program under the Community Service Grant scheme from the Indonesian Ministry of Research, Technology, and Higher Education. The activities focused on training in *Jatung Utang* performance as an effort to revitalize traditional music from Kalimantan amidst digital modernization. The project partner was the Benaong Foundation, with activities taking place in Baru Urban Village, Tenggarong District, Kutai Kartanegara Regency. The methodology encompassed outreach and socialization, basic technique training, mentoring for partner administrators, a festival serving as a platform for artistic expression, monitoring and evaluation, as well as the preparation of progress and final reports. The program engaged local residents and Dayak community leaders to ensure ethical knowledge transfer. Results indicated improved participant skills, increased public appreciation, and the establishment of a community-based preservation ecosystem adapted to the digital era.